An impact investing and blended finance framework for foundations to leverage impact capital - Hand, Geraldine Mary (Graduate School of Business (GSB), 2019)
With the right tools, South Africa’s endowed philanthropic foundations can use their full asset base to leverage traditional capital pools toward market-based solutions. These solutions address key socio-economic challenges of inequality, unemployment and poverty using investing for impact strategies and blending models. However, this is an opportunity not yet exploited in South Africa despite traction abroad. By developing case studies of six international foundations that have deployed impact investment and structuring strategies, this study formed an understanding of how key enablers to adoption of these strategies were utilised. Thereafter, the leaders of fourteen local foundations were interviewed to expose current practices and barriers to adoption. Subsequent focus groups were conducted to examine the outcome of the previous data collection process. Findings reveal that chief among the barriers is the lack of appreciation of Total Portfolio Management as an asset management strategy for foundations. The reasons advanced being, the role of investment advisors, application of fiduciary duty, and an understanding of the tax dispensation for foundations. Another barrier is the limited use of innovative blended funding models to leverage traditional investors who have a greater pool of financial resources to potentially finance solutions. The reasons advanced are leadership vision and structuring skills within foundations. This study contributes to theory and practice by providing an initial attempt as a toolkit for South African foundations to enable them to be more effective in catalysing much needed financial resources to alleviate the Country’s triple constraint (inequality, unemployment and poverty). In so doing, adding to the growing body of impact investing knowledge in South Africa.